Glycerol 3-Phosphate Inhibits Swarming and Aggregation of Myxococcus xanthus - Moraleda-Muñoz, Aurelio (American Society for Microbiology, 2001)
We have cloned a gene of Myxococcus xanthus with similarities to the permease for glycerol 3-phosphate (G3P) of other bacteria. Expression of the gene increased significantly during the first hours of starvation. Swarming of the wild-type strain was inhibited and aggregation was delayed by G3P. Conversely, a ΔglpT strain aggregated even on rich medium. These results indicate that G3P may function to regulate the timing of aggregation in M. xanthus.